Données préliminaires concernant l'élevage des jeunes de sandre (stizostedion lucioperca linne, 1758) en milieu saumâtre - Trandafirescu, I. I.; Ghițescu, Elena; Iliescu, M. (Cercetări Marine - Recherches Marines, 2026)
The paper presents the evolution of somatic, physiological and biochemical parameters in pike-perch fingerlings, collected from natural freshwater environment and then reared under experimental conditions at different salinity concentrations. The preliminary results obtained show faster growth rate and higher rate of accumulation of protein compounds in muscular tissue in the case of experimental groups maintained in higher salinity concentrations, comparative to control group reared in freshwater tanks.